Assessment of salt-affected soil in selected rice irrigation schemes in Tanzania: understanding salt types for optimizing management approaches - Omar, Moh’d M.; Massawe, Boniface H. J.; Shitindi, Mawazo J.; Pedersen, Ole; Meliyo, Joel L.; Fue, Kadeghe G. (Frontiers in Soil Science, 2024)
Salt-affected soils have serious implications for agricultural land quality and productivity, leading to a reduction in the net cultivable area available for food production. This issue has emerged as one of the foremost global challenges in recent years, impacting both food security and environmental sustainability. This research focuses on soil characterizations conducted in three irrigation schemes to understand the types, distribution, and nature of salt-affected soils. Auger observations served as the basic methodology for soil unit delineation in this study. Twelve representative soil pits with a depth of more than 160 cm were described, and undisturbed and disturbed samples were collected and analyzed for physical and chemical properties. The schemes were characterized by low levels of available phosphorus, organic carbon, and total nitrogen, as well as variations in exchangeable bases. Furthermore, 37.5% of the analyzed horizons highlighted the presence of salt-affected soils. Sodium was the predominant cation, followed by magnesium, potassium, and calcium. Likewise, HCO3 -was the dominant anion, followed by Cl -and SO4 2-. The results of this study reveal the existence of two types of salt-affected soil. Uturo irrigation scheme had sodic soils, while the Ndungu irrigation scheme had saline-sodic soils. Additionally, both sodic and saline-sodic soils have been discovered in the Mawala irrigation scheme. The root cause of this challenge is inherent soil conditions, exacerbated by inadequate drainage infrastructure. Therefore, measures such as the application of gypsum followed by salt leaching, improving soil drainage by incorporating organic matter, improving drainage infrastructure, and using rice-tolerant varieties are recommended to mitigate salt stress and improve soil fertility. It is imperative to establish a robust framework for continuous monitoring and regular assessment of soil health to enable timely interventions and informed decisions for sustainable agricultural management.